Capping of the exposed radicular surface. Part I - Grados Pomarino, Sixto (2005)
Gingival recession is defined as the displacement of the gingival margin apical to the Cementoenamel junction in one or more teeth. This mucogingival deformity can cause root hypersensitivity, poor esthetic appearance and cervical root caries. There are two main groups that can result in gingival recession, those derived from periodontal disease and those from traumatic origin. There are too some factors which are classified as predisposing and precipitant factors. Pathologically, gingival recessions derive from destruction of gingival connective tissue that reduces blood supply. Many procedures for surgical root coverage have been developed since introduction of laterally positioned pedicle flap, these include pedicle flaps, epithelialized free gingival grafts, connective tissue graft and guided tissue regeneration. The purpose of this article is to describe the clinical parameters and to mention the treatment options for this deformity.